PENGARUH PEMBATASAN JURNALISME INVESTIGASI TERHADAP HAK ATAS INFORMASI PUBLIK DAN PARTISIPASI PUBLIK DI INDONESIA - Syalaisha Nathania Faatihah; Agus Riwanto; Sri Wahyuni (Res Publica: Jurnal Hukum Kebijakan Publik, 2025)
AbstractThe right to public information is a fundamental human right and essential for public participation in democracy. However, the Broadcasting Bill (based on the second draft dated March 27, 2024, proposed by the Indonesian House of Representatives) contains provisions that restrict investigative journalism content, potentially reducing press independence and limiting freedom of expression. This study aims to analyze the impact of these restrictions on the right to public information and public participation in democracy. Using a normative approach and qualitative analysis, this research examines the compatibility of the provisions in the Broadcasting Bill with human rights principles as stated in Article 19 of the Universal Declaration of Human Rights and Article 28F of the 1945 Constitution of Indonesia. The findings indicate that restricting investigative journalism reduces public access to information and limits public participation in decision-making processes. Therefore, a reassessment of the provisions in the revised Broadcasting Law, particularly Article 50B Paragraph (2) Letter c, is necessary to ensure that journalists are not restricted from producing investigative journalism content. This would help safeguard freedom of information and prevent the weakening of active public participation in the democratic system.